Awareness of Consumers Rights: A study of Business and Service Class - Narwal , Mahabir; Gupta, Vivek (Gyan Management Journal, 2011)
Today producers try to increase their sale by all possible means. Some of the means adopted to increase ;ales serve the interests of the producers but are against the interests of the consumers. Although